2018
DOI: 10.1016/j.jot.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with knee osteoarthritis and patients with knee joint replacement as physically active as healthy persons?

Abstract: BackgroundIt is well documented that patients with knee osteoarthritis (KOA) suffer from reduced physical function and that function of the affected knee is improved after knee joint replacement (KJR). However, it remains uncertain whether patients with KOA are less physically active than healthy people and whether patients increase their level of physical activity after surgery to a level comparable with that of healthy people. The aim of this study was to examine whether patients with KOA are less physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Osteoarthritis (OA) is the most common form of joint disease and the leading cause of physical disability. 1,2 Increased prevalence of OA brings an enormous societal burden along with the aging population. 3 Therefore, a comprehensive understanding of the pathogenesis is conducive to develop an effective therapy for OA treatment.…”
mentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common form of joint disease and the leading cause of physical disability. 1,2 Increased prevalence of OA brings an enormous societal burden along with the aging population. 3 Therefore, a comprehensive understanding of the pathogenesis is conducive to develop an effective therapy for OA treatment.…”
mentioning
confidence: 99%
“…Physical activity studies were consistent in the number of sensors implemented, with 21 studies (81%) using a single sensor for activity measurements 35–40 42 43 45–57. As technology and availability of wearable accelerometers has progressed, the type of sensor used has also changed.…”
Section: Resultsmentioning
confidence: 85%
“…Twenty-six studies were identified as primarily focusing on physical activity following knee arthroplasty (tables 4 and 5), including a total of 1490 patients (58% women). Five of those studies included comparisons with a total of 620 end-stage OA patients without a knee replacement,35–38 though 458 of those patients came from a single report 37. Three studies compared physical activity levels of knee replacement patients with a total of 272 healthy controls 35 39 40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AM method used was found to work reliably in identifying activities in a semi‐free setting compared to human observers, with a classification accuracy of more than 97% 21,22 . In addition, activity monitoring following this or similar protocols has shown its value for research and outcome assessment in current literature 23,24 …”
Section: Methodsmentioning
confidence: 96%